Inequality of Opportunity in Early Childhood Development in Morocco over Time - El-Kogali, Safaa; Krafft, Caroline; Abdelkhalek, Touhami; Benkassmi, Mohamed; Chavez, Monica; Bassett, Lucy; Ejjanoui, Fouzia (World Bank, Washington, DC, 2016)
Early childhood development is a critical, but often neglected, phase of human development. Shortfalls in early childhood development have historically been a challenge in Morocco, with children facing unequal opportunities to develop because of the circumstances of their birth. This paper examines the roots of inequality in human and economic development in Morocco by focusing on the state of early childhood development, inequality in early childhood development, and trends over time, using several surveys conducted between 2003 and 2012. Large disparities exist in children's chances of healthy early childhood development based on the circumstances of their birth. There have not been consistent improvements in the levels of early childhood development or decreases in inequality over time. This study discusses critical directions for future policy on early childhood development to address the deficits and disparities identified.